Telemedicine in the Management of Chronic Heart Failure: Patient Outcomes and Satisfaction - Atiq Ur Rehman; Faiz Ullah; Khan, Rahim Dil; Naz, Fareeha; Ahmadyar; Khan, Ajmal (Indus Journal of Bioscience Research, 2025)
Introduction: Chronic heart failure (CHF) is one of the major global healthcare burdens manifested by recurrent hospitalizations. Telemedicine has now become considered a viable solution for the effective management of CHF since constant monitoring can be done, and timely intervention can also be taken. Objective: To assess the effectiveness of telemedicine and perceive the level of patient satisfaction in the case of chronic heart failure. Materials and Method: This study aims to identify various demographics and clinical characteristics of the study patients at Hayatabad Medical Complex Peshawar, Pakistan from April, 2024 to September 2024. One hundred and ten patients with NYHA Class II to IV heart failure were in the study using a structured telemedicine setup. Concerning the outcomes of the study, both the clinical and the patient satisfaction scores were evaluated. Results: Hospital readmissions reduced statistically from 36.4% to 16.4%, and emergency visits went down from 25.5 % to 9.1%. The NYHA class improved in more than 60% of the patients. Patient self-perceived satisfaction was high, and 87% of patients were highly satisfied using telemedicine, citing convenience and timely health care. Conclusion: Telemedicine is an effective tool that aids overall improvement in clinical outcomes and patients’ satisfaction in cases of CHF. It gives hope for an effective model of chronic disease management in low-resource countries.